Organizational Justice and Stress at Work of Bankers - Tárizi Cioccari Gomes; Vania de Fátima Barros Estivalete; Amanda Oliveira Ramadam (Revista Psicologia)
The objective of this research was to analyze the relationship between organizational justice and work stress, from the perspective of public and private banking sector employees from a city in the state of Rio Grande do Sul, Brazil. For this, a study was carried out with 339 employees of banking institutions, adopting as research instruments the Organizational Justice Perception Scale, the Stress at Work Scale and the reduced version of the Effort-Reward Imbalance Scale. Data analysis was performed using descriptive statistics, Cronbach’s alpha indicator, normality tests, Mann-Whitney test, Kruskal-Wallis test, Chi-square test and Correspondence Analysis. As a result, the relationship between the perception of organizational justice and stress at work is evidenced, demonstrating that the perception of justice contributes to the way employees face work situations and demands that can lead to stress.